PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCHDENGAN METODE TUGAS YANG DISERTAI RESITASI UNTUK MENINGKATKAN AKTIVITAS DAN HASILBELAJAR SISWA POKOK BAHASAN PROGRAMLINIER KELAS X BROADCASTING SMK NEGERI 1 JEMBER TAHUNAJARAN 2012/2013 - Ratnaningtyas, Nurina Anggun; Sunardi, S; Kristiana, Arika Indah (Kadikma, 2014)
Abstract. Cooperative learning model make a match type with a task accompanied recitation method is one of the techniques in learning models that provide opportunities for students to work together with others in which the application using the card as a medium to organize student interaction patterns supported by administration duties along with responsibility in the classroom to strengthen learning materials. This research aims to determine the application of these learning to improve the activities and student learning outcomes in the subject learning grade X of broadcasting linear program at SMKN 1 Jember. This research is a classroom action research using a qualitative approach. The results showed increased activity and student learning outcomes. Student activity increased from the first cycle with the percentage 69.8% to 89.42% in the second cycle. While the learning outcomes of students also increased from the first cycle with the percentage 78.57% to 85.71% in the second cycle. Key Words: Make a match, task method, recitation, linear program, student’s activities, student’s achievement